LIMITATIONS OF THE RIGHT TO THE PEACEFUL ENJOYMENT OF POSSESSIONS IN THE CASE-LAW OF THE EUROPEAN COURT OF HUMAN RIGHTS - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
The right to property is regulated by Article 1 of Protocol No. 1 to the European Convention on Human Rights. The basic aim of this article of the Convention is to protect every person from unlawful interference by the state in the peaceful enjoyment of property. Such a negative obligation includes, for example, the prohibition of expropriation of property, as well as the planning of restrictions or the temporary seizure of property. Any interference by a public authority with the right to peaceful enjoyment of property must be lawful, that is, it must have a basis in domestic law, which should be sufficiently precise and predictable. Also, the interference with the right to property must follow a legitimate aim. It is only permitted in the public interest, and control of the use of property is carried out in accordance with the general interest. The interests of an individual affected by a measure of violation of the right to property should be balanced with the interests of the general public. The interference should not represent an excessive or disproportionate burden on the individual. It is necessary for the state to introduce control measures that include determination whether a measure is appropriate for achieving its goal and whether it is proportionate. Interference in property rights does not constitute a violation of Protocol 1 to the Convention if the owner receives the appropriate compensation for damages, which constitutes a fair satisfaction.